2021
DOI: 10.1111/avsc.12563
|View full text |Cite
|
Sign up to set email alerts
|

Land‐use history determines stand structure and tree diversity in vanilla agroforests of northeastern Madagascar

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 99 publications
5
47
1
Order By: Relevance
“…Both kinds of agroforest thus resembled the land-use types they were derived from. An increase in accumulated amphibian species richness is also demonstrated from fallow-derived vanilla agroforest over fallow land, which may emphasize the rehabilitation opportunity of fallow land through agroforestry (Osen et al 2021). These findings are in line with the prediction from a recent study of Martin et al (2020) which found that the land-use history of agroforestry systems matters for biodiversity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both kinds of agroforest thus resembled the land-use types they were derived from. An increase in accumulated amphibian species richness is also demonstrated from fallow-derived vanilla agroforest over fallow land, which may emphasize the rehabilitation opportunity of fallow land through agroforestry (Osen et al 2021). These findings are in line with the prediction from a recent study of Martin et al (2020) which found that the land-use history of agroforestry systems matters for biodiversity.…”
Section: Discussionmentioning
confidence: 99%
“…We further show that while agroforestry systems play a limited role for rare amphibians, they may be more important for reptile species which prefer forest-derived vanilla agroforests over shifting cultivation and fallow-derived agroforests. Supporting the maintenance of existing forest-derived vanilla agroforests while avoiding the establishment of new forest-derived vanilla agroforests, which represent a forests degradation (Martin et al 2020;Osen et al 2021), should thus be set as a priority.…”
Section: Conservation Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the biodiversity value of vanilla agroforests may depend on land-use history, meaning whether the vanilla agroforest was established at the expense of forest (forest-derived), driving forest transformation, or whether it was planted on formerly fallow land (fallow-derived), rehabilitating formerly burned land (Martin et al 2020a). However, this important distinction is hardly made in land-use research (Martin et al 2020a), but research on plants (Osen et al 2021;Raveloaritiana et al 2021) and birds (Martin et al 2021) indicates differences in species richness and composition depending on land-use history, particularly for endemics.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the landscape of north-eastern Madagascar is characterized by a mosaic of forest fragments, rice cultivation (irrigated and rainfed), vanilla agroforests, and fallow lands (Zaehringer et al 2015). Vanilla agroforests are characterized by a combination of shade trees and Vanilla planifolia plants, leading to a structurally diverse habitat with medium to high canopy closure (Osen et al 2021). Woody and herbaceous fallows and rice paddy have significantly lower or no canopy closure and structurally and taxonomically simplified vegetation (Osen et al 2021).…”
Section: Introductionmentioning
confidence: 99%